DETERMINAN KESUKSESAN IMPLEMENTASI APLIKASI E-FAKTUR PAJAK - Tri Ciptaningsih (Jurnal Akuntansi, 2013)
This article discuss about the impact of e-tax invoice as the new tax aplication launched by the Directorate General of Taxation . In this article, we will explain about several rules that related to the main topic and Theory Acceptance Model (TAM). Explanation includes several factors which indicated influencing taxpayer behavior in e-tax invoice usage. Those factors are perceived usefulness, perceived ease of use, perceived of Fairness and trust, Norms, attitude, and behavioral intention. Key Words: e-tax invoice, theory acceptance model (TAM), and Tax compliance.